Development and Validation of 13-plex Luminex-Based Assay for Measuring Human Serum Antibodies to Streptococcus pneumoniae Capsular Polysaccharides - Danka Pavliakova (American Society for Microbiology, 2018)
ABSTRACT A Luminex-based direct immunoassay (dLIA) platform has been developed to replace the standardized pneumococcal enzyme-linked immunosorbent assay platform. The multiplex dLIA simultaneously measures the concentration of serum immunoglobulin G (IgG) antibodies specific for pneumococcal capsular polysaccharide (PnPS) serotypes 1, 3, 4, 5, 6A, 6B, 7F, 9V, 14, 18C, 19A, 19F, and 23F. The assay uses poly-l-lysine (PLL)-conjugated PnPS, chemically coupled to spectrally distinct Luminex microspheres. Assay validation experiments were performed using residual human serum samples obtained from 13-valent pneumococcal conjugate vaccine (13vPnC) clinical studies. Assay results are expressed as IgG antibody concentrations in micrograms per milliliter using the international reference serum, 007sp. The lower limit of quantitation (LLOQ) for all serotypes covered in the 13-plex dLIA fell within the range of 0.002 to 0.038 µg/ml serum IgG. The difference between the lower limit and upper limit of the assay range was >500-fold for all serotypes, and assay variability was <20% relative standard deviation (RSD) for all serotypes. IgG antibody measurements were shown to be serotype-specific (some cross-reactivity was observed only between the structurally related serotypes 6A and 6B as well as 19A and 19F), and no interference was observed between the serotypes when the assay was performed in the 13-plex format compared to the singleplex assays. The 13-plex dLIA platform developed by Pfizer Inc. generates up to 143 test results in a single 96-well plate and is a suitable replacement of the enzyme-linked immunosorbent assay (ELISA) platform for evaluating vaccine clinical trials. IMPORTANCE The pneumococcal enzyme-linked immunosorbent assay (ELISA) measures IgG antibodies in human serum, and it is an important assay that supports licensure of pneumococcal vaccines. The immune correlate of protection, 0.35 µg/ml of IgG antibodies, was determined by the ELISA method. Pfizer has developed a new Luminex-based assay platform to replace the ELISA. These papers describe the important work of (i) validating the Luminex-based assay and (ii) bridging the immune correlate of protection (0.35 µg/ml IgG) to equivalent values reported by the Luminex platform.